2016
DOI: 10.14687/jhs.v13i3.3975
|View full text |Cite
|
Sign up to set email alerts
|

Some variables predicting five factor personality of adolescents<p>Ergenlerin beş faktör kişilik özelliğini yordayan bazı değişkenler

Abstract: In this study, variables predicting the five-factor personality traits of adolescents were examined. These variables are cognitive flexibility, social self-efficacy, and cognitive errors. Research on middle and high school students from 7th.8th.9th.10th.11th.and 12th grades, a total of 441 students, participated to the study. In the study, the Five Factor Personality Inventory, Social Self Efficacy Scale, Cognitive Flexibility Scale and Cognitive Errors Questionnaire were used. The findings of the study show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…As a result of this situation, individuals can meet their social competence expectations in a healthy way. The said finding shows similarities with the studies by Bilgin (2009), Martin and Rubin (1995), and Martin and Anderson (1998), demonstrating a relationship between cognitive flexibility and social competence. Social competence, which directs the individual's cognitive structures, can enable the individual to have a flexible cognitive structure and decrease the attitudes leading to social media usage.…”
Section: Discussionsupporting
confidence: 81%
“…As a result of this situation, individuals can meet their social competence expectations in a healthy way. The said finding shows similarities with the studies by Bilgin (2009), Martin and Rubin (1995), and Martin and Anderson (1998), demonstrating a relationship between cognitive flexibility and social competence. Social competence, which directs the individual's cognitive structures, can enable the individual to have a flexible cognitive structure and decrease the attitudes leading to social media usage.…”
Section: Discussionsupporting
confidence: 81%
“…People with high cognitive flexibility are better at making changes on the fly and more easily than people with low cognitive flexibility (Cox, 1980). An individual with cognitive flexibility, on the other hand, is aware of options, able to deal with novel and challenging situations, produce alternate thoughts and ideas, and is better able to adapt to novel situations (Bilgin, 2009;Buğa et al, 2018;Martin & Rubin, 1995;Stahl & Pry, 2005).Some results of studies have shown that cognitive flexibility is related to the perceived stress level of cognitive flexibility (Buğa et al, 2018), problem-solving skills (Bilgin, 2009), anger (Diril, 2011), self-compassion (Martin et al, 2011), academic performance and openness to change (Lin, 2013), consciousness (Moore & Malinowski, 2009) and posttraumatic stress disorder, experiential escape and depression (Palm & Follette, 2011). Thompson and Shahen (2003) have argued that a person with these problem-solving skills should demonstrate cognitive flexibility.…”
Section: Introductionmentioning
confidence: 99%